Digital Financial Education for Economic and Financial Inclusion in Vulnerable Sectors of Peru - ORTIZ, Neptalí Rojas; TORRES, Joél Vásquez; RODRÍGUEZ, Víctor Hugo Puican (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024DO - 10.14505/tpref.v15.4(32).11, 2024)
The study explores the influence of digital financial education on the financial inclusion of workers in the construction sector in Peru. A quantitative approach with a non-experimental and cross-sectional design was used, applying a questionnaire to 128 self-employed workers. The results indicate a moderate influence of digital financial education on financial inclusion, with an R value of 0.541 and an R² of 0.292. The ANOVA analysis and the regression coefficients confirm the significance of the model (p < 0.001). Factors such as perception and trust in digital banking and integration of emerging technologies significantly influence financial inclusion. Most workers have a good level of digital financial literacy, although there is a need to improve training in digital tools; revealing that digital financial literacy is crucial for financial inclusion and sustainable economic growth, fulfilling Sustainable Development Goal 8.